Athena unbound : the advancement of women in science and technology - Etzkowitz, Henry, 1940- (Cambridge University Press, 2000)
Why are there so few women scientists? This book sets out to answer this question, and to propose solutions for the future. Based on extensive research, it reveals the hidden barriers, subtle exclusions and unwritten rules of the scientific workplace, and the effects, both professional and personal, that these have.